2009
DOI: 10.1512/iumj.2009.58.3633
|View full text |Cite
|
Sign up to set email alerts
|

Blow-up solutions for asymptotically critical elliptic equations on Riemannian manifolds

Abstract: Given (M, g) a smooth, compact Riemannian n-manifold, we consider equations like ∆ g u + hu = u 2 * −1−ε , where h is a C 1-function on M , the exponent 2 * = 2n/ (n − 2) is critical from the Sobolev viewpoint, and ε is a small real parameter such that ε → 0. We prove the existence of blowing-up families of positive solutions in the subcritical and supercritical case when the graph of h is distinct at some point from the graph of n−2 4(n−1) Scal g .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 26 publications
1
65
0
Order By: Relevance
“…That is, they reduce the problem to finding the critical point of a functional on the finite-dimensional manifold M . Our purpose in this paper is to obtain an analogous result to the result obtained in [8] for a more general class of functions f . In case that f (t) = t p−1 , the uniqueness of the least energy solution of problem (1.2) up to translations plays a crucial role.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…That is, they reduce the problem to finding the critical point of a functional on the finite-dimensional manifold M . Our purpose in this paper is to obtain an analogous result to the result obtained in [8] for a more general class of functions f . In case that f (t) = t p−1 , the uniqueness of the least energy solution of problem (1.2) up to translations plays a crucial role.…”
Section: Introductionmentioning
confidence: 72%
“…In [7], Hirano showed that the number of solutions of (P) is affected by the topology of suitable subset of M . More recently, Micheletti and Pistoia [8] studied the role of the scalar curvature for the multiple existence of positive solutions of (P) with f (t) = t p−1 . They showed that, for each C 1 -suitable critical set K, there exists a solution u ε of (P) under the assumption that the limiting problem…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present paper we build solutions to problem (1), which concentrate along an (m − 1)-dimensional submanifold of M as p goes to +∞. Moreover, for any integer k between 0 and (m − 3) solutions which concentrate along a k-dimensional minimal submanifold of M as p approaches the critical exponents 2 * m,k − 1 have been found in [14,11,4,7]. Therefore, it is natural to ask if it is possible to find solutions which concentrate along an (m − 2)-dimensional minimal submanifold of M as p approaches +∞.…”
Section: In Particular For ''Most'' Warping Functions F 'S and For 'mentioning
confidence: 95%
“…Indeed, it would be a geodesic if r 0 was a critical point of the warping function f (see [3]). In general r 0 is only a critical point of the function V f ,κ defined in (14). Remark 1.5.…”
Section: In Particular For ''Most'' Warping Functions F 'S and For 'mentioning
confidence: 99%